Protective mechanisms of Taiwanese green propolis toward high glucose‐induced inflammation via NLRP3 inflammasome signaling pathway in human gingival fibroblasts. (17th March 2021) - Vo, Thi Thuy Tien; Lee, Chiang‐Wen; Chiang, Yao‐Chang; Chen, Yue‐Wen; Yu, Yu‐Hsiang; Tuan, Vo Phuoc; Wu, Ching‐Zong; Lee, I‐Ta
Abstract: Objective: To investigate protective effects of Taiwanese green propolis (TGP) against high glucose‐induced inflammatory responses in human gingival fibroblasts (HGFs) through NLRP3 inflammasome signaling pathway. Background: NLRP3 inflammasome has been implicated in the progression of both diabetes mellitus and periodontitis, suggesting a common potential therapeutic target for these diseases. Propolis is renowned for various biological activities, particularly anti‐inflammation and antioxidant, representing a promising therapy for many conditions. However, underlying mechanisms remain unclear. Methods: The cytotoxicity of TGP was evaluated by cell viability assay. The mRNA levels and protein expression or secretion of various inflammatory molecules and NLRP3 inflammasome‐related molecules in high glucose‐exposed HGFs with or without pretreatment of TGP (5 μg/ml) were determined by real‐time PCR and western blot or specific kits, respectively. Intracellular and mitochondrial ROS measurements, NADPH oxidase activity determination, and subcellular fractions were performed to assess ROS generation. The transcriptional activity of NF‐κB was measured by luciferase reporter kit. The signaling components were further differentiated using pharmacological inhibitors of ROS and small interfering RNAs of TLR2, TLR4, or NF‐κB. Results: High glucose could induce IL‐1β‐driven inflammatory responses in HGFs via the activation of NLRP3 inflammasome regulated by TLR2/TLR4 coupled ROS in NF‐κB‐dependent manner. TGP had no adverse impact on the cell viability of HGFs at concentrations no greater than 10 μg/ml, and could exert inhibitory effects on high glucose‐induced inflammatory responses via the interruption of NLRP3 inflammasome signaling pathway. Conclusion: Taiwanese green propolis could elicit protective effects against IL‐1β‐driven inflammation in high glucose‐exposed HGFs through TLR2/TLR4 combined ROS/NF‐κB/NLRP3 inflammasome pathway.